2022
DOI: 10.1128/jvi.01050-22
|View full text |Cite
|
Sign up to set email alerts
|

Lab-Attenuated Rabies Virus Facilitates Opening of the Blood-Brain Barrier by Inducing Matrix Metallopeptidase 8

Abstract: The ability to change BBB permeability was associated with the pathogenicity of RABV. BBB permeability was enhanced by infection with lab-attenuated RABV instead of wt RABV, allowing immune cells to infiltrate into the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…When performing experiments with recombinant RABVs, we found that the recombinant CVS-M-G57E RABV could still cause some ATP and NAD reduction, suggesting that factors other than the M protein influence the energy metabolism of neurons. We hypothesized that this was due to the G protein of CVS, since it has been reported that the G protein of non-pathogenic RABV strains (such as the CVS strain) can trigger apoptosis, whereas the G protein of pathogenic strains (such as the DRV strain) induces less or no apoptosis ( 43 , 44 ), and activation of the apoptotic pathway inhibits mitochondrial metabolism ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…When performing experiments with recombinant RABVs, we found that the recombinant CVS-M-G57E RABV could still cause some ATP and NAD reduction, suggesting that factors other than the M protein influence the energy metabolism of neurons. We hypothesized that this was due to the G protein of CVS, since it has been reported that the G protein of non-pathogenic RABV strains (such as the CVS strain) can trigger apoptosis, whereas the G protein of pathogenic strains (such as the DRV strain) induces less or no apoptosis ( 43 , 44 ), and activation of the apoptotic pathway inhibits mitochondrial metabolism ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported that intracerebroventricular microinjection of MMP8-specific shRNA lentivirus could diminish the magnitude of ischemia-induced brain injury. MMP8 levels have been found to be elevated in patients with ischemic stroke and are closely associated with both BBB leakage and inflammatory responses 30 32 . Furthermore, BMSC transplantation has the potential to downregulate MMP8 levels, possibly by influencing the differentiation of BMSC into multiple lineages 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that neurotropic viruses enter the CNS by breaching the BBB ( 31 , 32 ). One study showed that laboratory-attenuated rabies virus, which is the same neurotropic virus as JEV, enhances BBB permeability ( 33 ).…”
Section: Discussionmentioning
confidence: 99%